Neurocognitive and mental health outcomes in children with tungiasis: a cross-sectional study in rural Kenya and Uganda - Berrick Otieno; Lynne Elson; Abneel K. Matharu; Naomi Riithi; Esther Chongwo; Khamis Katana; Carophine Nasambu; Francis Mutebi; Herman Feldmeier; Jürgen Krücken; Ulrike Fillinger; Amina Abubakar (BMC, 2023)
Abstract Background Tungiasis, a neglected tropical parasitosis, disproportionately affects children. Few empirical studies have reported neurocognitive and mental health outcomes of children with ectoparasitic skin diseases like tungiasis. Pathophysiology of tungiasis suggests it could detrimentally affect cognition and behaviour. This study pioneered the investigation of neurocognitive and mental health outcomes in children with tungiasis. Methods This was a multi-site cross-sectional study including 454 quasi-randomly sampled school-children aged 8-14 from 48 randomly selected schools in two counties in Kenya and a district in Uganda. The participants were stratified into infected and uninfected based on the presence of tungiasis. The infected were further classified into mild and severe infection groups based on the intensity of the infection. Adapted, validated, and standardized measures of cognition and mental health such as Raven Matrices and Child Behaviour Checklist were used to collect data. Statistical tests including a multilevel, generalized mixed-effects linear models with family link set to identity were used to compare the scores of uninfected and infected children and to identify other potential risk factors for neurocognitive and behavioural outcomes. Results When adjusted for covariates, mild infection was associated with lower scores in literacy [adjusted β(aβ) = − 8.9; 95% confidence interval (CI) − 17.2, − 0.6], language (aβ = − 1.7; 95% CI − 3.2, − 0.3), cognitive flexibility (aβ = − 6.1; 95% CI − 10.4, − 1.7) and working memory (aβ = − 0.3; 95% CI − 0.6, − 0.1). Severe infection was associated with lower scores in literacy (aβ = − 11.0; 95% CI − 19.3, − 2.8), response inhibition, (aβ = − 2.2; 95% CI − 4.2, − 0.2), fine motor control (aβ = − 0.7; 95% CI − 1.1, − 0.4) and numeracy (aβ = − 3; 95% CI − 5.5, − 0.4). Conclusions This study provides first evidence that tungiasis is associated with poor neurocognitive functioning in children. Since tungiasis is a chronic disease with frequent reinfections, such negative effects may potentially impair their development and life achievements. Graphical abstract